Transcriptomics of Wild‐Type Mice and Mice Lacking ADAMTS‐5 Activity Identifies Genes Involved in Osteoarthritis Initiation and Cartilage Destruction. Issue 6 (30th May 2013) - Bateman, John F.; Rowley, Lynn; Belluoccio, Daniele; Chan, Ben; Bell, Katrina; Fosang, Amanda J.; Little, Christopher B.
<x xml:space="preserve">Abstract</x> Objective To identify changes in gene expression in mice with osteoarthritis (OA) in order to explore the mechanisms of the disease. Methods Gene expression profiling was performed in cartilage from mice with surgically induced OA. We used wild‐type (WT) mice and Adamts5Δcat mice, in which ADAMTS‐5 activity is lacking and aggrecan loss and cartilage erosion are inhibited, to distinguish gene expression changes that are independent of ADAMTS‐5 activity and cartilage breakdown. Mechanical instability was introduced into the knee joints of 10‐week‐old male mice via surgical destabilization of the medial meniscus (DMM). Cartilage from the developing lesion in the destabilized medial meniscus and corresponding regions in sham‐operated joints was harvested by microdissection at 1, 2, and 6 weeks postsurgery, and RNA was extracted, amplified, and hybridized to whole‐genome microarrays. Results Several previously identified OA‐related genes, including Ptgs2, Crlf1, and Inhba, and novel genes, such as Phdla2 and Il11, were up‐regulated in both WT mice and Adamts5Δcat mice, indicating that they are independent of ADAMTS‐5 activity. The altered expression of other genes, including Col10a1, the sentinel marker of cartilage hypertrophy, and Wnt/β‐catenin pathway genes, required ADAMTS‐5 activity. Cell death pathway genes were dysregulated, and Tp53, Foxo4, and Xbp1 endoplasmic reticulum–stress transcriptional networks were activated. Analysis of degradome genes identified up‐regulation of many proteases, including Mmp3, Capn2, and the novel cartilage proteases Prss46 and Klk8. Comparison with other studies identified 16 genes also dysregulated in rat and human OA as priorities for study. Conclusion We have identified, for the first time, several genes that have an ADAMTS‐5–independent role in OA, identifying them as possible OA initiation candidates. This work provides new insights into the sequence of gene dysregulation and the molecular basis of cartilage destruction in OA.